Influence factors analysis and accuracy improvement for stress measurement using ultrasonic longitudinal critically refracted (LCR) wave. (1st December 2018) - Liu, Haibo; Li, Yapeng; Li, Te; Zhang, Xiang; Liu, Yankun; Liu, Kuo; Wang, Yongqing
Abstract: Generally, material stress measurement using ultrasonic longitudinal critically refracted (LCR) wave is inevitably influenced by ambient temperature and coupling condition, which limits its industrial application. In this article, the sensitivity of stress measurement accuracy to temperature variation and coupling condition is discussed analytically and numerically. Based on this, the ultrasonic signal-detecting mode is improved by one-transmitter-two-receiver signal-detecting configuration. Meanwhile, a novel coupling condition is also created by directly filling with couplant between the ultrasonic probe and the measured surface. The testing results showed that the temperature sensitivity could be reduced to 0.81 ns/°C compared with −16.82 ns/°C of the traditional one-transmitter-one-receiver signal detecting configuration, and less distortion and attenuation of the detecting LCR wave signals could also be obtained. Further, a pre-stretched aluminum alloy with uniaxial stress was employed to verify the feasibility of the developed method and probe. The stress measurement accuracy could achieve 20 MPa compared with the simulation results.